Power and the teaching of medical ethics. Issue 6 (1st December 1999) - Nicholas, B
Abstract : This paper argues that ethics education needs to become more reflective about its social and political ethic as it participates in the construction and transmission of medical ethics. It argues for a critical approach to medical ethics and explores the political context in medical schools and some of the peculiar problems in medical ethics education.